Efeito da aplicação do gás ozônio na resistência de união entre resina composta e dentina - RODRIGUES, Paula Cicília Faquim (2009)
The aim of this study was to evaluate the effect of ozone gas and its use with an antioxidant on the resin-dentin microtensile bond strength. The oclusal enamel of forty human third molars was then removed to expose a flat superficial dentin surface. The teeth were randomly divided into four groups (n = 10): (G1) untreated dentin with ozone (control group); (G2) ozone gas application for 40 s followed by acid etching; (G3) acid etching followed by ozone gas for 40s; and (G4) ozone gas for 40s with subsequent application of sodium ascorbato 10% for 10 min. Composite build-ups were constructed incrementally. Specimens were sectioned to obtain sticks with cross-sectional areas of 1mm2 to be tested in tension (0.5 mm/min). The microtensile bond strength values were analyzed by one-way ANOVA and Tukey s test (α=0.05). All sticks fractured were then observed under a stereomicroscope (40X). The results showed that the G1 had higher values of microtensile bond strength when compared to G2 and G3 (p=0.00). The values of microtensile bond strength of G1 and G4 were similar (p = 0158) and higher than the G2, but there was no difference between the values of G3 and G4 (p=0,115). The use of ozone prior to etching (G2) resulted in lower value of microtensile bond strength in all conditions evaluated (p = 0.00). The application of ozone gas decreased the microtensile bond strength of the interface dentin/composite resin, but the values were reversed when the use of sodium ascorbate